Characterization of Nicotiana tabacum genotypes possessing deletion mutations that affect potyvirus resistance and the production of trichome exudates - Kurtis L. Dluge; Zhongbang Song; Bingwu Wang; W. Tyler Steede; Bingguang Xiao; Yong Liu; Ralph E. Dewey (BMC Genomics, 2018)
Abstract Background Advances in genomics technologies are making it increasingly feasible to characterize breeding lines that carry traits of agronomic interest. Tobacco germplasm lines that carry loci designated VAM and va have been extensively investigated due to their association with potyvirus resistance (both VAM and va) and defects in leaf surface compounds originating from glandular trichomes (VAM only). Molecular studies and classical genetic analyses are consistent with the model that VAM and va represent deletion mutations in the same chromosomal region. In this study, we used RNA-seq analysis, together with emerging tobacco reference genome sequence information to characterize the genomic regions deleted in tobacco lines containing VAM and va. Results Tobacco genotypes TI 1406 (VAM), K326-va and K326 (wild type) were analyzed using RNA-seq to generate a list of genes differentially expressed in TI 1406 and K326-va, versus the K326 control. Candidate genes were localized onto tobacco genome scaffolds and validated as being absent in only VAM, or missing in both VAM and va, through PCR analysis. These results enabled the construction of a map that predicted the relative extent of the VAM and va mutations on the distal end of chromosome 21. The RNA-seq analyses lead to the discovery that members of the cembratrienol synthase gene family are deleted in TI 1406. Transformation of TI 1406 with a cembratrienol synthase cDNA, however, did not recover the leaf chemistry phenotype. Common to both TI 1406 and K326-va was the absence of a gene encoding a specific isoform of a eukaryotic translation initiation factor (eiF4E1.S). Transformation experiments showed that ectopic expression of eiF4E1.S is sufficient to restore potyvirus susceptibility in plants possessing either the va or VAM mutant loci. Conclusions We have demonstrated the feasibility of using RNA-seq and emerging whole genome sequence resources in tobacco to characterize the VAM and va deletion mutants. These results lead to the discovery of genes underlying some of the phenotypic traits associated with these historically important loci. Additionally, initial size estimations were made for the deleted regions, and dominant markers were developed that are very close to one of the deletion junctions that defines va.